COMPARISON OF THE EFFECTIVENESS OF RADIAL VERSUS FEMORAL ACCESS FOR DIAGNOSTIC AND THERAPEUTIC PROCEDURES IN PATIENTS WITH PERIPHERAL ARTERIAL DISEASE - KHAN , B; KHAN , AT; MUHAMMAD , A; SAWAR , S; RAHMAN , F; HASSAN , MU (Biological and Clinical Sciences Research Journal, 2023)
Peripheral arterial disease (PAD) is a medical condition in which the blood vessels outside the heart and brain were affected. The study’s main objective is to compare the effectiveness of radial versus femoral access for diagnostic and therapeutic procedures in patients with peripheral arterial disease. The research article aimed to compare the effectiveness of radial and femoral access for diagnostic and therapeutic procedures in patients with the peripheral arterial disease (PAD). The study was conducted in two hospitals in Peshawar, Pakistan - Hayatabad Medical Complex and Lady Reading Hospital. The study duration was from January 2020 to December 2020. A total of 384 patients were enrolled in the study, with 192 randomly assigned to the radial access group and 192 to the femoral access group. The study found that RA was associated with a significantly lower risk of major bleeding and access site complications compared to FA. Specifically, the incidence of major bleeding was 1.56% in the radial access group and 5.73% in the femoral access group (p=0.02), and the incidence of access site complications was 2.6% in the radial access group, 8.3% in the femoral access group (p=0.01). In conclusion, our study suggests that radial access is a safe and effective alternative to femoral access for diagnostic and therapeutic procedures in patients with peripheral arterial disease. Radial access is associated with lower rates of major bleeding and access site complications, particularly for diagnostic procedures, and may offer advantages such as faster patient ambulation and improved patient comfort.